(untitled) (International Journal of Contemporary Security Studies, 2024)
The special military operation that the Russian Federation launched on the territory of Ukraine on February 24, 2022, brings with it a number of problematic issues not only from the domain of military sciences but now increasingly specific security sciences (energy security, environmental security, food security, health security).